The first case of erythritol-induced anaphylaxis in Europe diagnosed with skin tests and basophil activation tests - Marco Dubini, MD; Patrizia Pignatti, PhD; Federica Rivolta, MD; Antonella Gurrado, BSc; Paolo Marraccini, MD (Journal of Allergy and Clinical Immunology: Global)
The use of erythritol as a food sweetener has spread significantly from Japan throughout the world. We describe a case of severe anaphylaxis due to immediate-type allergy to erythritol that was diagnosed with in vitro basophil activation tests and in vivo skin tests.